Evaluating the Stability of Co2P Electrocatalysts in the Hydrogen Evolution Reaction for Both Acidic and Alkaline Electrolytes - Zhang, Yue; Gao, Lu; Hensen, Emiel J M; Hofmann, Jan P (ACS energy letters, 2018)
The evaluation of the stability of emerging earth-abundant metal phosphide electrocatalysts by solely electrochemical current-potential sweeps is often not conclusive. In this study, we investigated Co2P to evaluate its stability under both acidic (0.5 M H2SO4) and alkaline (1.0 M KOH) hydrogen evolution (HER) conditions. We found that the electrochemical surface area (ECSA) of Co2P only slightly increased in acidic conditions but almost doubled after electrolysis in alkaline electrolyte. The surface composition of the electrode remained almost unchanged in acid but was significantly altered in alkaline during current-potential sweeps. Analysis of the electrolytes after the stability test shows almost stoichiometric composition of Co and P in acid, but a preferential dissolution of P over Co could be observed in alkaline electrolyte. Applying comprehensive postcatalysis analysis of both the electrode and electrolyte, we conclude that Co2P, prepared by thermal phosphidization, dissolves stoichiometrically in acid and degrades to hydroxides under alkaline stability testing.The evaluation of the stability of emerging earth-abundant metal phosphide electrocatalysts by solely electrochemical current-potential sweeps is often not conclusive. In this study, we investigated Co2P to evaluate its stability under both acidic (0.5 M H2SO4) and alkaline (1.0 M KOH) hydrogen evolution (HER) conditions. We found that the electrochemical surface area (ECSA) of Co2P only slightly increased in acidic conditions but almost doubled after electrolysis in alkaline electrolyte. The surface composition of the electrode remained almost unchanged in acid but was significantly altered in alkaline during current-potential sweeps. Analysis of the electrolytes after the stability test shows almost stoichiometric composition of Co and P in acid, but a preferential dissolution of P over Co could be observed in alkaline electrolyte. Applying comprehensive postcatalysis analysis of both the electrode and electrolyte, we conclude that Co2P, prepared by thermal phosphidization, dissolves stoichiometrically in acid and degrades to hydroxides under alkaline stability testing.